A new species of planthopper in the genus Haplaxius from Osa Peninsula in Costa Rica (Hemiptera: Fulgoroidea: Cixiidae) - Echavarria, Marco A. Zumbado; Barrantes Barrantes , Edwin A.; Bartlett, Charles R.; Helmick, Ericka E.; Kunz, Gernot; Bahder, Brian W. (Zootaxa, 2022)
Haplaxius is a large genus of New World cixiid planthoppers. The genus is of particular interest because Haplaxius crudus can transmit palm infecting phytoplasmas and the recent discovery of additional Haplaxius on palms during survey work highlights the need to fully understand the diversity of this genus on palms. Herein, a new species, Haplaxius cotinga sp. n., is described from the Osa Peninsula in Costa Rica. This species is most similar to H. deleter from southern Panama, from which it differs mostly by features of the male terminalia. Molecular data for the cytochrome c oxidase subunit I (COI), 18S rRNA, and histone 3 (H3) gene is provided and demonstrates supplemental support for placing the novel taxon in Haplaxius.